PREDICTING NURSES' TURNOVER INTENTIONS BY DEMOGRAPHIC CHARACTERISTICS, PERCEPTION OF HEALTH, QUALITY OF WORK, AND WORK ATTITUDES - Mahmoud Al-Hussami; Muhammad Darawad; Ali Saleh; Ferial Ahmed Hayajneh (European Scientific Journal, ESJ, 2013)
Aim: The purpose of this paper is to examine the impact of demographic variables, organizational commitment levels, perception of health, and quality of work on turnover intentions. Methods: A self-reported cross-sectional survey design was used to collect data from Jordanian registered nurses who were working between June 2011 and November 2011. Results: the findings showed strong effects of the quality of work, perception of health, and normative organizational commitments on turnover intentions. Conclusion: This study sheds the light on the important work outcomes in healthcare organizations. Increasing nursing quality of work and normative organizational commitment are good strategies for reducing turnover intentions.